ASSESSMENT OF GENDER-BASED TRANSPORT ACCESSIBILITY IN DUTSE, JIGAWA STATE - Ahijo, Tukur Mohammed; Barde, Bate Garba; Madu, Ijanu Emmanuel; Kura, Nura Umar; Abba, Nasiru Mustapha (FUDMA JOURNAL OF SCIENCES, 2026)
Transport accessibility is inadequate in the medium sized city of Dutse, Nigeria. This paper is the second in the series of papers that analyses traveller experience and understanding in Dutse from a gender perspective. Therefore, this study intends to know the transport accessibility knowledge of the genders in Dutse city based on their travels within the city. 400 questionnaires were administered across the 5 wards of Dutse city using random sampling. The findings shows that while there are similarities between the male transport accessibility challenges and the female there are still distinctions between the genders. Therefore, these distinctions are what is needed for transport planners in Dutse to understand to provide a transport system that is accessible for all genders. Recommendations for periodic quantitative and qualitative data collection and gender-disaggregated analysis, improving physical accessibility and affordability, first and last-mile connectivity, subsidized transport fare schemes for frequent trips to key destinations were proffered.